Regulación legal de la gestación subrogada y su incidencia en la protección jurídica-constitucional de la familia en el Perú, 2020 - Rengifo Arévalo, Xiomar Alexandra (2022)
Due to infertility that many people have been presenting, many of them have resorted to surrogacy to materialize their desires to have children and found a family. Surrogacy is a technique of assisted reproduction that in Peru, does not have a normative framework that regulates it in a certain way, according to the current advance of science in this field; situation that generates uncertainties about legal relationships, rights, duties and obligations regarding the conceived minor, the pregnant woman and the intended parents. The main objective of the study was to determine how a legal regulation about surrogacy, can have a favorable impact on the legal - constitutional protection of the family in Peru. The research was of basic type and exploratory level, with components of a dogmatic - legal and sociological - functional research. It was found in the results that an express legal regulation on surrogacy is going to have a favorable impact on the legal protection of the family, so through it the filiation of the minor with the intended parents is recognized. In addition to guaranteeing fundamental right for instance: the right to reproductive health, founding and protecting the family as well as the protection of the best interests of the child.